Development of Science Teaching Materials Using the CTL Approach to Improve Self-Control of Elementary School Students - Muthyara Daryus; Firman Firman (Psychocentrum Review, 2022)
This study aims to describe and develop science teaching materials using the CTL approach to improve self-control of fifth grade students at SD Negeri 21 Lubuk Lintah Padang which are valid, practical and effective. This type of research is development using a modified 4-D model. The results of this study are the average score of science teaching materials using the CTL approach with a validity value of 89.4% (valid). The results of practicality by the teacher obtained results of 87.5% (practical), and from the results of practicality by students obtained results of 84.5% (practical). The results of the effectiveness of using teaching materials get an average of 0.74 (effective). It can be concluded that science teaching materials use the CTL approach to improve self-control of fifth grade elementary school students which results are valid